College students' social capital and their perceptions of local and national cohesion - Núria Rodríguez-Planas; Alan Secor (Institute of Labor Economics (IZA), 2023)
Using Queens College (a four-year college in NYC public system) students' survey data from 2022/23, we find that vulnerable students have less social capital in terms of physical order and social support in their neighborhoods. While social capital is directly related to self-reported neighborhood and national cohesion, resilience, and better mental health, different components of social capital matter for specific demographics. Physical order is more salient for less vulnerable students while social support is more salient for vulnerable students. Our findings underscore the need for policy action to be tailored to specific groups, rather than following a one-size-fits-all approach.
Keywords: I24; 330; social cohesion; social capital; college students; mental health